Influence of polydispersity on the viscoelastic properties of linear polydimethylsiloxanes and their binary blends - Ressia, Jorge Aníbal (2000)
Linear polydimethylsiloxanes of relatively narrow molecular weight distribution (MWD) were synthesized by anionic polymerization and characterized by different techniques. Binary blends were also prepared with some of the synthesized polymers. Linear viscoelastic parameters, such as storage (G') and loss (G'') moduli, were obtained at different temperatures as functions of frequency (ω). The time temperature superposition principle was applied in order to increase the frequency range measured. Zero-shear rate viscosity (η0), steady-state recoverable compliance (J(e)0) and zero-shear rate first normal stress coefficient (ψ1.0) were calculated from the data corresponding to the terminal relaxation zone. The molecular weight dependence of those parameters shows a good agreement with classical models and previously reported results, although J(e)0 and ψ1.0 are strongly affected by polydispersity. Different polydispersity factors were applied in order to fit the experimental values of the viscoelastic properties with the theory.